The Role of Teachers in Supporting Student Learning Processes in School Learning Activities - Salsabila Ainimas Awaludin; Anggia Suci Pratiwi; Budi Hendrawan (CV. Ksatria Siliwangi, 2024)
Teachers play a very important role in shaping the quality of student learning processes at school. Learning is not only determined by the material presented, but also by how teachers design, implement, and assist students during learning activities. This study aims to describe the role of teachers in supporting the overall learning process of students, including learning planning, implementation of learning activities in the classroom, student guidance, learning evaluation, as well as supporting factors and obstacles faced by teachers. This study uses a descriptive approach involving two teachers who are directly involved in learning activities at school. Data was collected through written online interviews using WhatsApp chat, so that the informants could convey their experiences and views reflectively. The results showed that teachers played an active role in creating more meaningful learning through careful planning, selection of varied learning methods, and creation of a comfortable and conducive classroom atmosphere. Teachers also provide motivation and guidance to students, especially those who experience learning difficulties, thereby helping to increase student engagement and understanding. Support from the school environment and the availability of infrastructure are factors that help optimize learning, although limited facilities remain a challenge. This study shows that the consistent and continuous role of teachers contributes greatly to the success of the student learning process at school.